Viscoelastic Networks: Forming Cells and Tissues - Corominas-Murtra, Bernat; Petridou, Nicoletta I. (Frontiers in Physics, 2021)
Spatiotemporal changes in viscoelasticity are a key component of the morphogenesis of living systems. Experimental and theoretical findings suggest that cellular- and tissue- scale viscoelasticity can be understood as a collective property emerging from macromolecular and cellular interactions, respectively. However, linking the structural/material properties of cells and tissues, such as material phase transitions, to the microscopic interactions of their constituents, is still a challenge both at the experimental and theoretical level. In this review, we summarize work on the viscoelastic nature of cytoskeletal, extracellular and cellular networks. We then conceptualize viscoelasticity as a network theory problem and discuss its applications in cells and tissues. We propose that the statistical mechanics of networks can be used in the future as a powerful framework to uncover quantitatively the biomechanical basis of viscoelasticity across scales.